Good Corporate Governance in Sharia Banking - Zaisika Khairunnisak; Hashim Purba; Utary Maharany Barus; Idha Aprilyana (PT FORMOSA CENDEKIA GLOBAL, 2023)
Islamic banking business is growing in Indonesia. The implementation of sharia banking business is a tangible manifestation of the adoption of the Sharia Law System in Indonesia. Islamic banking business is carried out by Islamic banks. As a subject of law, in the implementation of Islamic banking business, Islamic banks are legally obliged to apply GCG Principles. The non-implementation of legal obligations to apply GCG Principles in the implementation of Islamic banking business creates legal liability for Islamic banks.This study discusses the application of GCG Principles in the implementation of Islamic banking business by Directors acting on behalf of Islamic banks. In this regard, this study is focused on examining the legal responsibility of Islamic banks due to the non-application of GCG Principles in the implementation of Islamic banking business.This research is a type of normative research. The method used in this study is the normative juridical research method. This research is a prescriptive analysis, using various types of data as appropriate in legal research.